2007
DOI: 10.1093/beheco/arm081
|View full text |Cite
|
Sign up to set email alerts
|

Signaling by decorating webs: luring prey or deterring predators?

Abstract: Many organisms convey false signals to mislead their prey or predators. Some orb-weaving spiders build conspicuous structures on webs called decorations. Web decorations and spider colorations are both suggested to be important signals involved in interactions between spiders and other organisms. There are several hypotheses about the functions of signaling by decorations, among which prey attraction had received much support, but empirical evidence regarding predator defense is controversial. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 48 publications
2
51
1
Order By: Relevance
“…Blackledge, 1998;Blackledge and Wenzel, 1999), while others finding that they attract prey (e.g. Craig and Bernard, 1990;Cheng and Tso, 2007). One reason for these contradictory findings is that different-shaped decorations differ in their visual attractiveness to predators and prey, and thus may serve different functions (Cheng et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Blackledge, 1998;Blackledge and Wenzel, 1999), while others finding that they attract prey (e.g. Craig and Bernard, 1990;Cheng and Tso, 2007). One reason for these contradictory findings is that different-shaped decorations differ in their visual attractiveness to predators and prey, and thus may serve different functions (Cheng et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Cheng and Tso provided direct field evidence that A. aemula on webs with cruciate decorations experienced significantly more wasp attacks than those on undecorated webs (Cheng and Tso, 2007). These results (Cheng and Tso, 2007) and those of laboratory studies using Y-mazes (Bruce et al, 2001;Seah and Li, 2001) showed that predators may use cruciate form decorations to locate the spiders. However, responses of wasps to Argiope spiders on webs with linear decorations seem to differ.…”
Section: Discussionmentioning
confidence: 90%
“…According to the morphological phylogeny of the family Araneidae (Scharff, 1997), decoration building evolved independently several times among various genera. Most genera of spiders build linear decorations, and the cruciate form decorations can only be found in certain subadult and adult Argiope spiders The ratio of probabilities of two certain events is designated as e Cheng and Tso, 2007). The intergenus evolutionary relationship of decoration forms within the family Araneidae is congruent with the intra-genus evolutionary relationship of decoration forms in Argiope spiders.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Only when spiders had stayed on their webs for more than 4 h, were their data used in data analyses (Cheng and Tso, 2007). Data from 174 h of video recording of spiders were used to investigate the effect of decoration on the predation and prey interception rate of webs.…”
Section: Field Observationsmentioning
confidence: 99%